Analysis of rain fade mitigation using site diversity technique in southern tropical region of India - Harika, S; Nagarjuna, S; V. Naveen, T; Sanjay Harshanth, G; Ch. Sri Kavya, K; K. Kotamraju, Sarat (International Journal of Engineering and Technology, 2017)
In order to design a reliable earth to satellite microwave link at certain frequencies in tropical region due to multi propagation we come across fading which means variation of attenuation of a signal with time, geographical position and radio frequency. The radio waves propagating through the earth atmosphere is attenuated due to the presence of atmospheric particles such as water vapor, rain drops and the ice particles which absorb and scatter the radio waves and consequently degrade the performance of the microwave link and there is probability of loss of signal strength, to mitigate this problem Site Diversity Technique is used from the different Fade Mitigation Techniques. The analysis of Site Diversity Gain Model based on the measured rainfall data has been done.Â Â